Emerging Trends in Peripartum Hysterectomy; A High Alert in Obstetrics - Aqsa Ikram-ul-haq, Nadia Sadiq, Shama Bashir, Nabeela Waheed, Nargis Shabana, Umme Aqsa (Journal of Rawalpindi Medical College, 2021)
Introduction: The high incidence of lower segment caesarean section (LSCS) leading to morbidly adherent placenta and making it a leading cause of peripartum hysterectomy. Objective: Peripartum hysterectomy is one of the major obstetrical procedures that need to be performed electively/emergency in patients having morbidly adherent placenta (MAP) for the sake of the patient’s life. Need to conduct this study arises because we want to highlight the increasing rate of peripartum hysterectomy secondary to MAP, the emerging trend of increased LSCS in our socio-demographic strata, and its effects on maternal morbidity and mortality. Materials and Methods: This was a retrospective study which was carried out in the Department of Obstetrics and Gynaecology Unit II, Holy Family Hospital, Rawalpindi. All patients who underwent peripartum hysterectomy were included in the study. Data was collected from record files and labor room registers in accordance with ethical guidelines. Results: Out of 11,440 deliveries in one year, 60 patients underwent peripartum hysterectomy with an incidence of 5.2 per 1000 deliveries. The majority of patients (87%) fell in the age group of 25-33 years. 4(6.6%) patients undergone peripartum hysterectomy for postpartum hemorrhage (PPH) due to uterine atony, 3(5%) due to the ruptured uterus, and 53(88%) due to MAP. All patients who had undergone a peripartum hysterectomy due to MAP were previously scarred for LSCS (100%). 5% with previous 1 LSCS, 31% with previous 2 LSCS, 44% with previous 3 LSCS and 18% with previous 4 LSCS. Conclusion: The high incidence of peripartum hysterectomies in young patients secondary to MAP highlights the need for critical review and audit of indications of primary LSCS and repeat LSCS. It also highlights the need for expertise at the time of surgery to decrease the rate of maternal morbidity and mortality.